Live Virtual Machine Migration Techniques, Survey and Research Challenges - Kumar, Sheetal; Malhotra, Deepti (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is a vibrant technology in today’s world. It delivers a platform independent service which is reliable, scalable, on demand etc. Cloud computing rely on allocating resources to achieve reliability and economy of extent similar to utility, Virtualization is key concept of cloud computing, it is a technique which allow multiple operating system run simultaneously on single physical server, it is used for balancing the loads on servers, managing the fault occurred and uses comprehensive strategy for energy consumption and system maintenance. There are two type of techniques used in migration i.e., pre copy and post copy, this research paper discusses study of various types of VM live migration, their classifications and relative scrutinizing of these methodologies and challenges in migrating virtual machine.